Memória digital e educação a distância: reflexões acerca da disciplina Letramento Digital da UAB-UFSCar - Schiavinato-Batista, Ana Carla (Universidade Federal de São Carlos, 2018)
Think about forms of organization and relationship of the current society has been a great challenge, given the speed of changes, many of them as a result of the electronic and digital innovations, particularly those relating to digital information and communication technologies (DICT). There are significant changes in how we learn and teach, how data are moving, how people relate to one another and how society is organized. Several concepts in this context arise and/or are transformed, among of these concepts are the memory and the "digital memory". Therefore, aiming to understand how the "digital memory" is presented in the type of education which is called "distance education" (EaD) was the thesis’ purpose, so that it was possible to analyze how the "digital memory" affect this context, and then, to reflect on educational´s background in a society marked by digital technologies. The research methodology used was based on assumptions of the Critical Theory of Society as a qualitative analysis of data to be observed in the model of distance education of UAB-UFSCar, in the discipline called "Literacy Digital", which was taught to the students of Bachelor's Degree in Music Education course. At that were specifically observed aspects of form and content of the VLE (virtual learning environment): tools/design and didactic materials. It is concluded that is necessary to think about the impacts of "digital memory" like: short-term logic, loss of the present as transforming the future, hyperstimulation of the senses that modify the feeling of the which has been lived continuously. Therefore, it was proposed to combat engendered logics by the technological society that help to bombard the short-term memory with useless and superficial information and data, making it dificult for more complex creation processes which needs some time and pauses to be consolidated in long-term memories which will be rescued and re-elaborated in the future.
Digital memory and distance education: reflections on the training in the context of the "Digital Lettering" discipline of UAB-UFSCar
Keywords: Memória digital; Educação a distância; Tecnologias digitais; Teoria crítica; UAB-UFSCar; Digital memory; Educational backgorund; Distance education; Digital technologies; Critical theory; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO